ASPECTOS DO CRESCIMENTO E DA REPRODUÇÃO DE- Ipomoea acuminata ROEM. ET SCHULT.- CONVOLVULACEAE - Maimoni-Rodella, Rita C. S.; Rodella, Roberto Antonio (REVISTA DE AGRICULTURA, 2015)
ASPECTOS DO CRESCIMENTO E DA REPRODUÇÃO DE- Ipomoea acuminata ROEM. ET SCHULT.- CONVOLVULACEAE